IMPROVING THE EFFECTIVENESS OF COUNSELLING AND CLINICAL EXAMINATION OF PATIENTS IN A FAMILY POLYCLINIC (Intent Research Scientific Journal, 2023)
To date, graduate students of medical universities are experiencing some difficulties in carrying out a comprehensive clinical examination of patients with the interpretation of the data obtained and the differential diagnosis. At the end of the training, the graduate must have the skill of conducting a clinical examination of the patient with the definition and solution of his problems, including preventive measures and medical examinations. In our opinion, in order to correct the above, it is necessary: to modernise and systematise training in medical examination of patients both in a hospital and in a family polyclinic; to determine the specific goals and objectives of the actions performed by students when consulting patients in need of both the 1st, 2nd, and 4th categories of services; and to create criteria for evaluating students for the stages and levels of examination of patients.The work of a family doctor requires a wide variety of knowledge and skills. This includes clinical experience to correctly assess the situation; knowledge of pathophysiology to understand the causes of deterioration or improvement of the patient's condition; data from clinical studies to assess the prognosis and correct treatment; and knowledge of the deontology and psychology of the patient to help him make arrangements in case of loss of independence. All this knowledge will be needed at the same time; knowing one thing in such a situation is absolutely not enough. To feel confident, a family doctor must constantly take care of the completeness of his knowledge; at the right moment, he will be able to select what the patient needs and effectively solve his problems.